Performance analysis of still image compression based on SPHIT compression technique: article / Muhammad Fitri Rahmat - Rahmat, Muhammad Fitri (2012)
The high demand on storage capacity at low bit rate in transmission has opens an interest among researcher to integrate new compression technique to meet demand requirement in the future. In this paper, a set of wavelet functions (orthogonal and biorthogonal) is tested using 256 x 256 still images samples in different image format (PNG, JPEG and TIFF) and numbers of level decomposition (3, 4, 5) based on SPHIT compression technique. The performance analysis discussed wavelet transform features in still image compression and the quality of the image performance is degraded by level of compression and decompression process using MATLAB software. The image quality is measured based on PSNR, MSE and compression ratio performance, The result sholvs that suitable number of decomposition is 4. This number of decomposition gives high PNSR and good visual quality performance.